Towards a new strategy for International Cultural Relations in the European Union? An analysis of European Cultural Diplomacy as a resource of soft power - Tomás López, Ana (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
With this paper we intend to elucidate whether cultural diplomacy and international relations continue to constitute one of the main resources of soft power of the European Union, as instruments capable not only of enhancing its influence and leadership as a global actor, but also of generating key strategies to confront the great challenges that the Union is facing today. To this end, we will propose a series of recommendations for the preparation and implementation of a new strategy for European cultural diplomacy and international cultural relations, adapted to the current legal, geopolitical, social and health circumstances.